Trocar site HERnias after Bariatric Laparoscopic Surgery (HERBALS): a prospective cohort study - Karampinis, Ioannis; Lion, Eliette; Hetjens, Svetlana; Vassilev, Georgi; Galata, Christian; Reißfelder, Christoph; Otto, Mirko (Obesity surgery, 2020)
The exact prevalence of trocar site hernias after bariatric procedures is not yet known. Recent metaanalysis data indicated concerning rates of up to 25%. We conducted a prospective cohort study to estimate the prevalence and analyze the role of fascia closure in the development of trocar hernias.
Gesehen am 01.12.2021